What do we learn about the Swacch Bharat Mission from the NFHS-5 fact sheets? - Dean Spears; Nathan Franz; Diane Coffey (Institute of Labor Economics (IZA), 2021)
How much did rural sanitation in India change under the five years of the Swacch Bharat Mission? The best nationally representative statistics on sanitation in India have long come from the Demographic and Health Surveys, known as the National Family and Health Surveys in India. The fifth round, conducted in 2019 and 2020, was interrupted by the pandemic, but limited summary statistics have been released for some states. Here we analyze these statistics. We conclude that about half of the rural population in the four large Indian states of Bihar, Madhya Pradesh, Rajasthan, and Uttar Pradesh continued to defecate in the open at the end of the Swacch Bharat Mission.
Keywords: O15; 330; India; sanitation; open defecation; Swacch Bharat Mission; SBM; NFHS